Perancangan Sistem E-Arsip Digital Dokumen Akademik Prodi Teknologi Informasi Universitas PGRI Silampari Angkatan 2024 - Nadia Anjani Putri; Wandini Nurul Hidayah; Perdiansyah; Muhammad Taufiq Abdul Haq (Proceeding of Silampari Conference of Life Science and Technology, 2026)
Academic document management in higher education requires a structured system for easy storage and access. In the Information Technology Study Program at PGRI Silampari University, student academic document management still faces challenges such as slow archive retrieval, the risk of document loss, and poorly organized storage. Therefore, this research was conducted to design a digital e-archive system that can assist the academic document management process for students enrolled in the class of 2024 more effectively and efficiently. The method used in this research is the System Development Life Cycle (SDLC), which includes needs analysis, system design, implementation, and system testing. The result of this research is a web-based digital e-archive system that can simplify the process of storing, managing, and searching academic documents more quickly, securely, and in a structured manner, thereby increasing the efficiency of archive management within the study program.